THE URGENCE OF AMENDMENT TO ACT NUMBER 1 OF 2009 RELATED UNMANNED AERIAL SYSTEMS - Nurul Fatimatus Sholihah; Adya Paramita Prabandari (Jurnal Cendekia Hukum, 2022)
Discovery Unmanned Aerial Systems/UAS is used in various fields such as reconnaissance tools, topological mapping, and recreational purposes. This must be balanced with legal arrangements because there are many misuses of UAS operations. Act No. 1 of 2019 concerning Aviation, which is the legal umbrella for aviation in Indonesia, does not mention the term UAS. This writing aims to explain the urgency of changing Act No. 1 of 2009 regarding UAS arrangements based on 3 basis for the formation of legislation. This writing uses a comparative approach. The urgency of the changes to the Aviation Law are 1) to maintain the security of Indonesia in accordance with the mandate of the 1945 Constitution (philosophical basis), 2) the increasing use and development of UAS technology and the need for regulations covering the types of land, water, seabed and ground-based drones that do not just flying in the air (sociological basis), 3) the potential for new types of law violations (juridical basis). 2) Aviation Act doesn’t give direct mandate to technical regulations that have legal force to regulate UAS.